Japanese interpretations of “pain” and the use of psychomimes - Asano-Cavanagh, Yuko (2016)
This chapter examines six Japanese psychomimes — zuki-zuki, kiri-kiri, shiku-shiku, chiku-chiku, hiri-hiri, and gan-gan — that express subtle differences in states or sensations regarding “pain”. It is generally recognized, however, that many languages lack words with the same meanings as these Japanese psychomimes and that their meanings are difficult to capture precisely. The definitions in Japanese-English dictionaries, for example, are not sufficient to explain the exact meanings and there is also the problem that each Japanese expression can correspond to several English verbs. This study applies the framework of the Natural Semantic Metalanguage approach to explicate the meaning of the six Japanese psychomimes. It makes reference to a corpus of naturally-occurring examples compiled from publicly available sources from physicians, patients, hospitals, and pharmaceutical companies. The analysis indicates that each psychomime conveys a vivid metaphorical meaning. The quality of the pain is suggested by reference to an imagined scenario of something moving inside a part of the body or touching part of the body. This imagined ‘something’ can be understood as something ‘sharp’ or as something similar to ‘fire’ or to ‘metal’. The use of psychomimes is an effective and efficient way for expressing and understanding “pain” in Japanese.